Characterization of lactic acid bacteria isolated from Malaysian foods - Amiri, Azin; Foo, Hooi Ling; Tai, Hui Fong; Chuah, Li Oon; Loh, Teck Chwen (2012)
Lactic Acid Bacteria (LAB)are a group of Gram positive bacteria,which are industrially important microorganisms due to their vast applications in various industries. In this study, 10 LAB isolates namely CB1, I-1, OMR1, TB-1, UP2, TP5, GP8, RW18, B12-M9 and Big-2-Y isolated from Malaysian foods were characterized phenol typically and genotypically. The genotypic characterization technique employed in this study was 16SrDNA-Polymerase Chain Reaction amplification, where a pair of universal primers: 8FPL16S and 149216S was used to amplify the 16S rDNA. The amplicon with approximate size of 1.5kb was then purified and analysed for DNA sequence. Based on the results of 16Sr DNA sequence, the isolates of CB1,TB-1 and UP2 were identified as Pediococcus acidilactici, whereas isolates of I-1, OMR1 and B12-M-9 were identified as Pediococcus pentosaceus and the other 4 isolates namely TP5, GP8, RW18 and Big-2-Y were identified as Lactobacillus plantarum with 100% homology. Carbohydrate fermentation profiles were determined for phenotypic characteristics, where the results of API50CHL kits showed more than 90% homology for all tested isolates, which were in agreement with the results of 16Sr DNA analyses. Antibiotic resistance profile was also determined according to the Kirby-Baueragar diffusion test using antibiotic impregnated disks. All tested LAB isolates showed resistance to nalidixic acid, streptomycin, vancomycin, gentamycin, kanamycin and bacitracin. However, they were sensitive to tetracycline, chloramphenicol, erythromycin and penicillin G. It is important to determine the antibiotic resistance profile of LAB isolates prior to their application in respective industry since the results in his study showed that some LAB isolates are resistant to several antibiotics being used commonly in livestock industry as growth promoter and disease treatment.